EVALUASI IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM MENINGKATKAN STANDAR PROSES DAN STANDAR PENDIDIK DI SMK - Rosi Octariantoni; Hendri Marhadi; M. Nur Mustafa (Jurnal Manajemen Pendidikan, 2026)
This study aims to evaluate the implementation of School-Based Management (SBM) in improving Process Standards and Educator Standards at SMK Abdurrab Pekanbaru. The study used a qualitative approach with evaluative methods. Data were collected through interviews, observations, and documentation, then analyzed using reduction, presentation, and conclusion-drawing techniques. The results showed that the implementation of SBM has been effective in supporting school management, characterized by independence in decision-making and active participation of school residents. Process Standards were well met through practice-based learning that increased student engagement and competence. Meanwhile, Educator Standards showed that teachers have adequate competence, although learning innovation and technology utilization still need to be improved. Overall, SBM has made a positive contribution to the quality of education, but strengthening aspects of digitalization and pedagogical innovation are needed to support continuous improvement in the quality of education.